Electrospinning of PVDF nanofibers incorporated cellulose nanocrystals with improved properties (vol 30, pg 885, 2023) - Aydemir, Deniz; Sozen, Eser; Borazan, Ismail; Gunduz, Gokhan; Ceylan, Esra; Gulsoy, Sezgin Koray; Bardak, Timucin (Springer, 2023)
[Abstract Not Available]